Reproductive tract neoplasia in adult female Asian elephants (Elephas maximus). Issue 6 (November 2021) - Landolfi, Jennifer A.; Gaffney, Patricia M.; McManamon, Rita; Gottdenker, Nicole L.; Ellis, Angela E.; Rech, Raquel R.; Han, Sushan; Lowenstine, Linda J.; Agnew, Dalen; Garner, Michael M.; McAloose, Denise; Hollinger, Charlotte; et al.
Recent reports have highlighted a lower-than-expected prevalence of neoplasia in elephants and suggested mechanisms for cancer resistance. But despite infrequent reports in the literature, uterine neoplasia is common in managed Asian elephants ( Elephas maximus ). This study is an archival review of reproductive tract neoplasia in 80 adult female Asian elephant mortalities in managed care facilities in the United States from 1988 to 2019. Neoplasms occurred in 64/80 (80%) of cases. Most were in the uterus (63/64; 98%) with only a single case of ovarian neoplasia. Myometrial leiomyomas were present in 57/63 (90%) cases with uterine neoplasia. Uterine adenocarcinoma was present in 8/63 (13%) cases. Remaining cases included endometrial adenoma (2), focal carcinoma in situ in endometrial polyps (1), anaplastic carcinoma (1), endometrial hemangioma (1), primitive neuroectodermal tumor (PNET; 1), and angiosarcoma (1). One case with uterine adenocarcinoma had a separate pelvic mass histologically characterized as an anaplastic sarcoma. Distant metastases were documented in 5/8 (63%) cases of uterine adenocarcinoma, and in the uterine anaplastic carcinoma, PNET, and angiosarcoma. Four uterine adenocarcinomas and one carcinoma in situ were examined immunohistochemically for pan-cytokeratin, vimentin, and estrogen receptor. In all, neoplastic cells were pan-cytokeratin positive and vimentin negative, and in 2 cases were immunoreactive for estrogen receptor. Results show that female reproductive tract neoplasia, particularly of the uterus, is common in Asian elephants and is not limited to leiomyomas. Importantly, uterine neoplasms have the potential to impact fecundity and may represent obstacles to conservation in managed care.